How an Immigrant Buddhist Institution Negotiates Belonging in Poland: The Case of Thiên Phúc Pagoda - Grabowska, Ewa (Journal of intercultural studies, 2022)
Migrant religious institutions tend to be focal places of intercultural encounters, serving as spaces for performing national, ethnic and religious identities, as well as, dialoging and negotiating belonging within the majority society. Thiên Phúc, a Vietnamese-operated pagoda functioning in Poland, serves as an important factor in the Vietnamese migrant community affairs, at the same time remaining virtually unknown to a broader Polish public. Drawing on extensive fieldwork study results, we adapt an original perspective of a migrant religious institution as an active agent in negotiating belonging to various social contexts, namely the host society, the Vietnamese migrant community and the social space of Buddhist religious institutions. We point out to coherences and disjunctures between arguments formulated during the search for legitimisation from the diverse sources. We also reflect upon complex ways in which the negotiation strategies are related to Polish public discourse on the Vietnamese community, which tends to form two opposite arguments: one calling for better integration, the other for their isolation and invisibility. Doing so, we shed light on outcomes and limitations of particular strategies of negotiating belonging undertaken by an ‘otherized’ institution in the context of one of the most ethnically and religiously homogeneous societies in Europe.